Characteristics of wave energy resources on coastal waters of northeast Taiwan. (January 2023) - Chen, Y.-L.; Lin, C.-C.; Chen, J.-H.; Lee, Y.-H.; Tzang, S.-Y.
Abstract: Hourly measurements of wave data for 10–14 years from four field stations were analyzed to evaluate wave energy resource characteristics in medium wave power potential coastal waters of northeast Taiwan. Spectral parameters, resource index, and constitutive energy periods were discussed. Time series of water surface displacement in each hour for three consecutive years at two stations were first adopted to obtain period transferring coefficient C ep of 0.86–0.87 for JONSWAP's peak enhancement factor γ of 1.5–1.6. The derived average wave energy scatter maps characterized indices of monthly and seasonal variations and highlighted the effects of typhoon and higher potentials by monsoons with increasing waves from NE. Comparisons with previous numerical simulations on sites offshore northeastern coasts pointed out slightly higher energy potentials at present field stations suggesting field measurements being vital for resource assessment. From energy scatter maps of two representative geographical zones, 15 and 16 top-ranked bin conditions were selected to display concentrations on constitutive energy periods from 6 s to 10 s. Similar selections were applied to foreign energy resources in Pacific and Atlantic coastal waters to show major energy potentials at higher latitudes concentrated on constitutive period ranges by 2 s longer.